Augmentation of pulmonary reactions to quartz inhalation by trace amounts of iron-containing particles. - Castranova, V (1997)
Fracturing quartz produces silica-based radicals on the fracture planes and generates hydroxyl radicals (.OH) in aqueous media. .OH production has been shown to be directly associated with quartz-induced cell damage and phagocyte activation in vitro. This .OH production in vitro is inhibited by desferrioxamine mesylate, an Fe chelator, indicating involvement of a Fenton-like reaction. Our objective was to determine if Fe contamination increased the ability of inhaled quartz to cause inflammation and lung injury. Male Fischer 344 rats were exposed 5 hr/day for 10 days to filtered air, 20 mg/m3 freshly milled quartz (57 ppm Fe), or 20 mg/m3 freshly milled quartz contaminated with Fe (430 ppm Fe). High Fe contamination of quartz produced approximately 57% more reactive species in water than quartz with low Fe contamination. Compared to inhalation of quartz with low Fe contamination, high Fe contamination of quartz resulted in increases in the following responses: leukocyte recruitment (537%), lavageable red blood cells (157%), macrophage production of oxygen radicals measured by electron spin resonance or chemiluminescence (32 or 90%, respectively), nitric oxide production by macrophages (71%), and lipid peroxidation of lung tissue (38%). These results suggest that inhalation of freshly fractured quartz contaminated with trace levels of Fe may be more pathogenic than inhalation of quartz alone.